2013
DOI: 10.3766/jaaa.24.10.5
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic versus Electrical Coupling of Personal Frequency Modulation (FM) Receivers to Cochlear Implant Sound Processors

Abstract: Individuals with contemporary sound processors may show more favorable speech-recognition performance in noise electromagnetically coupled FM systems (i.e., Oticon Arc), which is most likely related to the input processing and signal processing pathway within the CI sound processor for direct input versus telecoil input. Further research is warranted to replicate these findings with a larger sample size and to develop and validate a more objective approach to fitting FM systems to CI sound processors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…Schafer and colleagues evaluated speech recognition in noise of nine CI recipients using the Oticon Arc (Copenhagen, Denmark) induction neckloop and the Oticon R2 directly coupled receiver in Advanced Bionics (Valencia, CA), Cochlear Ltd. (Cochlear, Sydney, Australia), and MED-EL (Innsbruck, Austria) implant users. 20 They found significantly better performance with the induction neckloop when the two systems were evaluated at default receiver settings. However, they reported equivalent results for the two systems when the gain of each receiver was adjusted to according to procedures recommended in the American Academy of Audiology (AAA) Fitting and Verification Guidelines (2008).…”
Section: Remote Microphone Rf Technologies Used With Cismentioning
confidence: 96%
See 4 more Smart Citations
“…Schafer and colleagues evaluated speech recognition in noise of nine CI recipients using the Oticon Arc (Copenhagen, Denmark) induction neckloop and the Oticon R2 directly coupled receiver in Advanced Bionics (Valencia, CA), Cochlear Ltd. (Cochlear, Sydney, Australia), and MED-EL (Innsbruck, Austria) implant users. 20 They found significantly better performance with the induction neckloop when the two systems were evaluated at default receiver settings. However, they reported equivalent results for the two systems when the gain of each receiver was adjusted to according to procedures recommended in the American Academy of Audiology (AAA) Fitting and Verification Guidelines (2008).…”
Section: Remote Microphone Rf Technologies Used With Cismentioning
confidence: 96%
“…Researchers have conclusively shown that both types of systems provide a significant improvement in speech recognition in noise compared with use of a CI alone. 18,20,21 However, the comparison of performance with induction neckloop with directly coupled systems led to mixed results. Schafer and colleagues evaluated speech recognition in noise of nine CI recipients using the Oticon Arc (Copenhagen, Denmark) induction neckloop and the Oticon R2 directly coupled receiver in Advanced Bionics (Valencia, CA), Cochlear Ltd. (Cochlear, Sydney, Australia), and MED-EL (Innsbruck, Austria) implant users.…”
Section: Remote Microphone Rf Technologies Used With Cismentioning
confidence: 99%
See 3 more Smart Citations